Copper-catalyzed construction of (Z)-benzo[cd]indoles: stereoselective intramolecular trans-addition and SN–Ar reaction. Issue 40 (30th September 2022) - Wang, Xinyue; Zeng, Heyang; Zhang, Wenli; Guo, Haiyang; Jin, Tao; Shi, Senlei; Jin, Xiaoyuan; Qu, Na; Liu, Li; Zhang, Lianpeng
Abstract : Copper-catalyzed one pot synthesis of polysubstituted benzo[ cd ]indoles is reported. Preliminary mechanistic studies indicated that the reaction undergoes intramolecular trans -addition and SN -Ar reaction with excellent regioselectivity. Abstract : Substituted benzo[ cd ]indoles are one of the most attractive frameworks because of their wide range of biological and optical activities. Herein, a copper-catalyzed one-step synthesis of biologically important polysubstituted benzo[ cd ]indoles starting from 8-alkynyl-1-naphthylamine derivatives is reported. In this protocol, many substituents tolerated the reaction conditions and produced ( Z )-benzo[ cd ]indoles in good yields. Preliminary mechanistic studies indicated that the reaction proceeds via a stereoselective intramolecular trans -addition and SN –Ar reaction with high selectivity and high yields. The synthesized polysubstituted ( Z )-benzo[ cd ]indoles possess sulfonamide building blocks, which make them candidates for bioactive molecules.